Pengaruh Strategi Pembelajaran Inquiry terhadap Kemampuan Berpikir Kritis dalam Pembelajaran PAI - Novia Dwi Ferlita; Rafiqah Alya; Gusmaneli Gusmaneli (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to analyze the effect of the inquiry learning strategy on students' critical thinking skills in Islamic Education (PAI) learning. The research employed a quantitative approach using an experimental design to examine the effectiveness of the strategy in improving students’ learning outcomes. The subjects of the study consisted of students who were divided into two groups, namely an experimental group and a control group. The experimental group received instruction through the inquiry learning strategy, while the control group was taught using conventional teaching methods commonly applied in classroom learning activities. Data collection was carried out through critical thinking tests and classroom observations to obtain comprehensive information regarding students’ learning processes and achievements. The results of the study indicate that students taught using the inquiry learning strategy experienced a significant improvement in their critical thinking skills compared to students who learned through conventional methods. Therefore, the inquiry learning strategy is proven to be effective in enhancing students’ critical thinking skills in PAI learning. This study is expected to become a useful reference for educators in developing more innovative, interactive, and student-centered learning strategies in the educational process.